Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I want to show the convergence of newton's algorithm when calculating the root of $f(x)=xe^x$ using an $x_0 \geq 0$.

The resulting recursion is

$$x_{k+1} = x_k - \frac{f(x_k)}{f'(x_k)} = x_k - \frac{x_k e^{x_k}}{x_ke^{x_k}+e^x}$$

Any hints? The only estimate I got so far was

$$|x_{k+1} - 0| = |x_k - \frac{x_k}{x_k+1}| \leq \quad?$$

$$|x_{k+1} - x_k| = |x_k - \frac{x_k}{x_k+1} - x_k| = |\frac{x_k}{x_k+1}| \leq \quad1?$$

where $f(0)=0$ is the root.

share|cite|improve this question
You might first identify $x^*$, then correct your computation of $f(x_k)/f'(x_k)$. – Did Feb 2 '13 at 17:05
Well, $f(x)=xe^x$ is Lipschitz Continuous (It is everywhere differentiable). – Inquest Feb 2 '13 at 22:32

You've made an error in computing $f'$, which likely accounts for your confusion. We should have $f'(x)=e^x+xe^x=(x+1)e^x$ by product rule, so since $e^x>0$ for all real $x$, then $$x_{k+1}=x_k-\frac{x_ke^{x_k}}{(x_k+1)e^{x_k}}=x_k-\frac{x_k}{x_k+1}.$$ See if you find that more tractable to work with.

Also, as a side note, since $e^x\neq 0$ for any $x$, you should be able to explicitly determine what the unique root of $f(x)$ is.

share|cite|improve this answer
The root is $f(0)=0$. I got the $f'$ wrong. But now thinking about it using the proper one I still don't manage to show convergence.. – fritz Feb 2 '13 at 22:23

Note that $f'(x)=(x+1)\mathrm e^x$ hence $x_{k+1}=u(x_k)$ where $u:x\mapsto x^2/(x+1)$.

Since $u(x)\lt x$ for every $x\gt0$ and $x_0\gt0$, the sequence $(x_k)_{k\geqslant0}$ is decreasing and converges to $0$. Assume without loss of generality that $x_0\lt1$. Then $x_{k+1}\lt x_k^2$ for every $k$ hence $$ x_k\leqslant(x_0)^{2^k}. $$ To refine this, note that $x_k=(x_0)^{2^k}/z_k$, where $$ z_k=\prod_{i=0}^k(1+x_i). $$ The sequence $(z_k)_k$ is increasing. Since $x_i\leqslant(x_0)^{2^i}$ and $x_0\lt1$, the series $\sum\limits_ix_i$ converges, hence the sequence $(z_k)_k$ is bounded. Finally, calling $z$ the limit of $(z_k)_k$, one gets $$ \lim\limits_{k\to\infty}x_k\cdot(x_0)^{-2^k}=z^{-1}. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.